Correlation of middle and upper Proterozoic strata of the northern rim of the North Atlantic craton - Young, Grant M. (Earth and Environmental Science Transactions of the Royal Society of Edinburgh, 1979)
Synopsis On the western and eastern sides of the North Atlantic craton, rocks between about 1·7 b.y. and 1·2 b.y. old are represented by thick basinal assemblages. Thin platformal successions cover the intervening region. The clastic component of these rocks was largely derived from the southeast where the Elsonian orogen might have been an important source terrane. Widespread mafic igneous activity (about 1·2 b.y. ago) in the central platformal region preceded orogenic movements in the basinal areas (Racklan-Carolinidian-Grenville orogeny). The Grenville orogen may have contributed significant amounts of clastic debris for a second cycle of sedimentary accumulation(∼ 1·2 b.y.–∼ 0·8 b.y.). The upper part of this cycle typically contains red beds and evaporites and, in the North American Cordillera, shows evidence of contemporaneous block faulting and extensional tectonism. These movements culminated in the East Kootenay and Hayhook orogenies and ushered in a third period of deposition about 850 m.y. ago. The third sequence includes glaciogenic rocks in the Cordilleran and East Greenland geosynclines. The basic geotectonic elements (platforms and geosynclines) of the North Atlantic craton were established as much as 1·7 b.y. ago, but continental fragmentation on the borders of the craton may not have taken place until early Phanerozoic times.